2016
DOI: 10.3390/jimaging2010004
|View full text |Cite
|
Sign up to set email alerts
|

Imaging for High-Throughput Phenotyping in Energy Sorghum

Abstract: The increasing energy demand in recent years has resulted in a continuous growing interest in renewable energy sources, such as efficient and high-yielding energy crops. Energy sorghum is a crop that has shown great potential in this area, but needs further improvement. Plant phenotyping-measuring physiological characteristics of plants-is a laborious and time-consuming task, but it is essential for crop breeders as they attempt to improve a crop. The development of high-throughput phenotyping (HTP)-the use of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Many studies have demonstrated the value of image-based sorghum phenotyping technologies for assessment of plant growth and development (Neilson et al 2015 ; Batz et al 2016 ; Thapa et al 2018 ; Masjedi et al 2020 ). In this study, the ARIS phenotyping platform was shown to be useful for collecting nondestructive measurements of green plant area (GPA) in sorghum.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated the value of image-based sorghum phenotyping technologies for assessment of plant growth and development (Neilson et al 2015 ; Batz et al 2016 ; Thapa et al 2018 ; Masjedi et al 2020 ). In this study, the ARIS phenotyping platform was shown to be useful for collecting nondestructive measurements of green plant area (GPA) in sorghum.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Batz et al (2016) demonstrated imaging for high-throughput phenotyping in energy sorghum. At ICRISAT, a high-throughput phenotyping platform called the "LeasyScan" facility has been established to measure leaf area quicker so as to access the dynamics of leaf development and leaf conductance, traits that are the focus for plant drought adaptation in ICRI-SAT mandate crops including sorghum.…”
Section: Next-generation Phenotypingmentioning
confidence: 99%
“…Since UAV platforms can significantly improve the spatial and temporal resolution of field images, they are increasingly used in precision agriculture to maximize crop yield and to protect crops from losses [19,20]. To accelerate breeding and genetics research, many types of imaging sensors, such as RGB [21,22], multispectral [23,24], and thermal [25,26], are used on UAVs for mapping phenotypes at the plot or plant scale resolution [27][28][29]. The increasing capabilities of such remote sensing techniques are continuously pushing boundaries improves the accuracy of plant-height estimates [54].…”
Section: Introductionmentioning
confidence: 99%